PENGARUH METODE PEMBELAJARAN DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Wulandari Asri (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
To determine effect the interaction methods of learning and interest in learning outcomes civic. Theresearch method was experimental. The sample size 50 students selected at random. The datacollection includes data on learning outcomes civic (Y), effect of methods of learning (X1) and theinterest in learning (X2). Data on learning outcomes civic (Y) using an objective test which consistedof your choices, with a scoring technique in the form of correct answer were given a score of 1 andincorrect answer were given a score of 0. For interest in learning (X2) using the Likert scoring withfive alternative answers. There is a significant interaction effect of learning method and interests ofthe student learning outcomes civics. From the results of calculations using ANOVA show that Fhitung= 11,270 which was higher than the value of Ftabel = 3,94 (Fh = 11,270 > Ft = 3,94). This means thatH0 refused and H1 accepted, so there is a significant interaction effect of learning method and interest